PENGUNGKAPAN CSR TERHADAP ASIMETRI INFORMASI - Frans Sanjaya; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
This research’s objective is to find out the relationship between CSR disclosure and information asymmetry. The measurement of CSR disclosure is using guideline from GRI G3.1. The measurement of information asymmetry is using bid-ask Spread. In this research control variable is also used, the control variables are earnings persistence and audit commitee. This research was carried out on go public companies in Indonesia which published their annual report and bid ask prices in the 2008 – 2015. The result of this research showed that the CSR disclosure has negative effect on information asymmetry, the earnings persistence has negative effect on information asymmetry, and the audit commite has effect on information asymmetry.